Modelling of a virtual power plant using hybrid automata. Issue 17 (28th February 2019) - Javaid, Chaudhry Jibran; Allahham, Adib; Giaouris, Damian; Blake, Simon; Taylor, Phil
Abstract : Virtual power plant (VPP) is a hybrid power system with a mesh of distributed resources, local loads and storage with both discrete and continuous variables involved. Control of such system requires advanced control schemes to make distributed assets act together to mimic an actual power plant. Previously, to study the behaviour of such systems, complex algorithms and modelling tools have been used but this paper proposes the use of Hybrid Automata (HA) as a convenient tool to model these systems. To demonstrate this, HA is used to model a VPP for a research farm owned by Newcastle University as a first step to design the control for the system.